"Being Absorbed in That Environment…It’s Just So Beneficial” – The Experiences of Physiotherapy Students in a Situated Learning Pilot Study - Barradell, Sarah; Blackstock, Felicity C; Tang, Clarice Y; Leo, Joan (International Journal of Practice-based Learning in Health and Social Care, 2017)
In this article, we aim to add to the existing literature on practice-based education. First, we will present a form of situated learning, which involved piloting a new teaching and learning relationship between the university and healthcare setting. Second, we will examine how students made sense of this perspective of practice. Using a phenomenologically oriented approach, this pilot study explored the experiences of entry-level physiotherapy students learning in a classroom environment, facilitated by clinicians, and located on a healthcare partner’s site. Twenty students completed two concurrent, theoretically oriented subjects that did not involve traditional clinical practicum experience. Two individual semi-structured interviews were conducted with students. Data was thematically analysed using an inductive approach. Three inter-related themes emerged. First, meaning-making is enhanced by the relevance and authenticity afforded by immersion in a practice-oriented classroom environment where clinicians facilitate learning. Second, learning from those ‘in practice’ challenges students’ professional and academic accountability. Finally, new educational infrastructures influenced students’ agency in unanticipated ways. This work highlights that students valued contextual learning. While meaning-making was enhanced by the development of key new relationships with others and the environment, these relationships also influenced student agency. Recommendations for health professional curricula are discussed, and include: capitalising on learning with peers, bringing the hidden curriculum into view and creating opportunities for students to navigate uncertainty and change.